Advances in accounting education teaching and curriculum innovations. Vol. 3 - Ketz, J. Edward; Schwartz, Bill N. (Advances in accounting education : teaching and curriculum innovations, 2000)
This is a refereed, academic research annual whose purpose is to meet the needs of individuals interested in ways to improve their classroom instruction. The book aims to offer thoughtful, well-developed articles that are readable, relevant and reliable. Articles may be either empirical and non-empirical. They emphasize pedagogy, that is, explaining how teaching methods or curricula/programmes can be improved.